2009
DOI: 10.1017/s0007114509991875
|View full text |Cite
|
Sign up to set email alerts
|

A controlled study of consumption of β-glucan-enriched soups for 2 months by type 2 diabetic free-living subjects

Abstract: Type 2 diabetes is associated with a higher cardiovascular risk and there has been a growing interest in using dietary intervention to improve lipid profile and glucose control. The present work aims at analysing the effects of the enrichment of a normal diet with b-glucan (3·5 g/d) in free-living type 2 diabetic subjects for 2 months, using a palatable soup. This trial was a parallel, placebo-controlled, double-blinded randomised study performed in fifty-three type 2 diabetic subjects. During a 3-week run-in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
80
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 28 publications
0
80
0
1
Order By: Relevance
“…The quality scores were between 3 and 4 according to the JADAD scale. Subjects were between 26 and 75 years, with a sample size of 18 and 97 participants [8,18]. Cugnet-Anceau et al [8] evaluated the intake of 3.5 g/day of β-glucans in soup, in T2D patients (BMI of 20-35 kg/m 2 ) for 2 months.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality scores were between 3 and 4 according to the JADAD scale. Subjects were between 26 and 75 years, with a sample size of 18 and 97 participants [8,18]. Cugnet-Anceau et al [8] evaluated the intake of 3.5 g/day of β-glucans in soup, in T2D patients (BMI of 20-35 kg/m 2 ) for 2 months.…”
Section: Resultsmentioning
confidence: 99%
“…Epidemiologic studies have suggested that dietary fibres such as β-glucan, a non-starch viscous polysaccharide derived from oat, are known to exhibit hypercholesterolemic effects, furthermore protecting against CHD [8]. …”
Section: Introductionmentioning
confidence: 99%
“…74 Cugnet-Anceau y Cols. 75 Wolever y Cols. Efectos del consumo del beta-glucano de la avena sobre el colesterol sanguíneo: una revisión Un 78% de los estudios encontraron efectos hipocolesterolemiantes del beta-glucano de avena, lo que coincide con la revisión realizada por Othman y Cols.…”
Section: Efecto Reductor Del Colesterol Sanguíneo Asociado Al Consumounclassified
“…As a result, various studies have been done investigating non-pharmacological form of treatments such as physical activity and functional food to reduce the side effect of diabetes. 3 Low glycaemic food consumption is a very fruitful alternative in controlling diabetes. 4 Foods that are rich in fiber are on the top of the glycaemic index and the potential component is beta glucan.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Studies have suggested that food products containing beta-glucans could reduce hyperglycemia. 3,4 Reyna et al 2003, suggested that the fiber build a barrier to prevent nutrients including glucose from being absorbed in the small intestine and consequently reducing insulinemia, glycaemia and cholesterol levels. 8 Studies that have been examining the impacts of beta glucans in people who are more likely to develop metabolic syndrome are frequent, however, the evidence of consuming oat beta-glucan to enhance glycaemia and insulin levels are not well established.…”
Section: Introductionmentioning
confidence: 99%